PENGEMBANGAN INSTRUMEN TES PILIHAN GANDA UNTUK MENGUKUR TINGKAT KEMAMPUAN BERPIKIR MATEMATIKA SISWA SMA - Rolina Amriyanti Ferita; Mia Fitria (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2019)
This research is development research that aims to develop multiple-choice test questions. The desired test question is valid, reliable with a good level of difficulty, good distinguishing power, and troublemaker that serves to measure the thinking skills of high school students in mathematics. This research was carried out by procedure 1) determining the purpose of the test, 2) making a test box, 3) conducting a review and revision based on the advice of the material and evaluation experts, 4) conducting a trial, and 5) conducting an item analysis. Results of analysis produce four questions is invalid, the value of r = 0.844 to r table 0.4438 which means reliable test questions, there are two questions that are not good or difficult, there are two questions that no distinguishing features are good, there are three questions that distractor does not function and there is one question that is omitted so that each thinking skill has the same number of questions based on the calculated r so that 12 multiple-choices test questions are valid, reliable, have a good level of difficulty and good distinguishing power, and functioning distractors. The results of the measurement of students 'thinking skills obtained that students' thinking skills were still at a low level.